A phononic rectifier based on carbon schwarzite host–guest system*Project supported in part by the National Natural Science Foundation of China (Grant No. 11890703), Science and Technology Commission of Shanghai Municipality, China (Grant Nos. 19ZR1478600 and 18JC1410900), and the Fundamental Research Funds for the Central Universities, China (Grant No. 22120200069). This work was partially supported by CREST JST (Grant Nos. JPMJCR19Q3 and JPMJCR19I1). Z. Z. gratefully acknowledges financial support from China Scholarship Council. (December 2020) - Zhangz 张, Zhongwei 忠卫; Ouyang 欧, Yulou 阳宇楼; Chen 陈, Jie 杰; Volz, Sebastian
Abstract : Thermal rectification is a promising way to manipulate the heat flow, in which thermal phonons are spectrally and collectively controlled. As phononic devices are mostly relying on monochromatic phonons, in this work we propose a phononic rectifier based on the carbon schwarzite host–guest system. By using molecular dynamic simulations, we demonstrate that the phononic rectification only happens at a specific frequency of the hybridized mode for the host–guest system, due to its strong confinement effect. Moreover, a significant rectification efficiency, ∼ 134 %, is observed, which is larger than most of the previously observed efficiencies. The study of length and temperature effects on the phononic rectification shows that the monochromaticity and frequency of the rectified thermal phonons depend on the intrinsic anharmonicity of the host–guest system and that the on-center rattling configuration with weak anharmonicity is preferable. Our study provides a new perspective on the rectification of thermal phonons, which would be important for controlling monochromatic thermal phonons in phononic devices.